FAKTOR-FAKTOR YANG MEMPENGARUHI PENGETAHUAN PERAWAT TENTANG PENANGANAN PERTAMA PASIEN GAWAT DARURAT DI RUANG IGD,ICU,NICU DAN BEDAH PADARUMAH SAKIT UMUM KAREL SADSUITUBUN LANGGUR MALUKU TENGGARA - Roynald Letelay, Stephen; Rustanti, Elly; Soraya Niah, Najah (LPPM STIKES HUSADA JOMBANG, 2020)
The first handler for emergency patient (PPGD) is one of the efforts that a person shouid immediately do if hef fids a victim who needs it ,therefore every individual , espec cially health workers must know it . The research design used was analitytic with the aim of tinding out the reration ship between the level of know ledge of nurses regarting the handling of the first emergency patients in the general hospitak in karel sadsaitubun langgur ,sout heast Maluku district.The population in this study were all nurses who performend nursing action in the general hospital karel sadsaitubun langgur general hospital namely in the IGD, TRIGGER,TRYGGER,and surgical room .While the sample taken was a total sample of 52 respondent .Primary data were obtained through questionnaires , while secondary data were obtained from the medical records of the general hospital in karel sadsaitubun langgur mall,south east Maluku and liferaturestudies .Data processing using a kumputer with descriptive univatiate statistical analysis and presentendin the from of a trequency descriptive table the resuts of this study indicate that know ledge of the first treamet of emergency patiets is 44 parsen will –informed 56 persen are lacking one thing that also became aphenomenon turnedout that most of the nurses studied were nurses who had just served in the general hospital karel sadsaitubun langgur neverreceived training or new theories about emergency ,emergencies. The conclusion of this study is the level of nurses knowledge about the first handling of emergency patients is still low and not as expected therefore yhe authors suggest to hospital management to make training.